Hedge fund masters : - Kiev, Ari (Wiley, 2005)
Discover the psychological strategies that hedge fund traders use to maximize their success in Hedge Fund Masters. Author Ari Kiev interviewed over 80 hedge fund traders, including some of the most successful hedge fund operators in the world, to illustrate the principles of success. Filled with in-depth insights and practical advice, the book explores the pressures felt by professional hedge fund traders as they manage enormous sums of their clients' money and shows you how to maintain emotional balance, focus on targets and goals, overcome deep-seated psychological obstacles, and trade with consistency and discipline.